THE EFFECT OF PRIMARY CAREGIVERS ON ATTACHEMENT IN INFANTS - Dervis, Bulent; Tuner, Tuna (International Scientific Journal Vision, 2024)
Attachment theory is a joint work of Bowlby and Mary Ainsworth. Bowlby established the basic principles of the theory based on the concepts of the child’s attachment to the mother and the disruption of this attachment through separation, loss and death. Mary Ainsworth created the theory of attachment theory by conducting research and projects on attachment. Ainsworth formulated the concept of maternal sensitivity to the child’s signals and its role in the development of child-mother attachment patterns and stated that the attachment figure is a safe base for the child to use while exploring the world. Parents’ approach to their children and the way they raise them primarily affect the psychological structure of children. Children shape their relationships in other periods of their lives with the behavioral styles they see in their family. At this point, it also affects the social structure. In addition, it is thought that attachment patterns have an important place in determining the social-emotional competencies of individuals. In this study, it was tried to review how attachment patterns differ according to life stages, the continuity of attachment patterns formed in the first years of life and the relationships between attachment patterns and social-emotional competencies.